2009
DOI: 10.1016/j.jmwh.2009.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Risk Distortion: Finding the Balance

Abstract: Pregnancy and birth have been conceptualized as medically problematic, with all pregnant women considered at risk and in need of medical monitoring. Universal application of risk scoring and surveillance as preemptive strategies in an effort to reduce risk is now standard obstetric practice. Labeling women "high risk" can result in more unnecessary interventions and have negative psychologic sequelae. When perceived pregnancy risk is out of proportion to the real risk, and when risk management procedures are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 58 publications
0
78
0
1
Order By: Relevance
“…Feelings of helplessness and a loss of control affect birthing expectations negatively. Admission during pregnancy causes more stress and negative emotions (Jordan and Murphy, 2009). Lee et al (2007) describe helplessness as a feeling that nothing can be done to solve the problem (Lee et al, 2007).…”
Section: Emotional Adaptation and Acceptancementioning
confidence: 99%
“…Feelings of helplessness and a loss of control affect birthing expectations negatively. Admission during pregnancy causes more stress and negative emotions (Jordan and Murphy, 2009). Lee et al (2007) describe helplessness as a feeling that nothing can be done to solve the problem (Lee et al, 2007).…”
Section: Emotional Adaptation and Acceptancementioning
confidence: 99%
“…Studies of risk perception show an individual's perception of risk is a subjective response based on previous life experiences, coping strategies, the context in which the risk occurs, the degree of perceived control, and the weight attached to information about the risk obtained from a variety of sources (Alaszewski and Horlick-Jones 2003;Edwards et al 2002;Gray 2006). This is also true of risk perception in pregnancy (Jordan and Murphy 2009;White et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, an individual's perception of risk is a subjective response based not only on statistical information, but also on previous life experiences, coping strategies, the context in which the risk occurs, and the weight attached to information about the risk obtained from a variety of sources (Edwards, Elwyn et al 2002;Alaszewski and Horlick-Jones 2003). This is equally true of risk perception in pregnancy (White, McCorry et al 2008;Jordan and Murphy 2009) Once a pregnant woman has been identified as experiencing a complication which poses a higher degree of risk to her or her fetus, she will be offered an enhanced level of obstetric care in order to optimise their safety (NICE 2010). For this care to be acceptable to women there must be some agreement between them and healthcare professionals about the need for the treatment and the form it should take.…”
Section: Introductionmentioning
confidence: 99%
“…a probability of 1/100. This allows the risk to be considered in its own terms (Jordan and Murphy 2009). Relative risk would be a comparison with another group, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation